PELATIHAN KETERAMPILAN PENULISAN BERITA ONLINE PADA MAHASISIWA BARU ANGKATAN 2023 DI UNIVERSITAS HALU OLEO - Iba, La; Jopang, Jopang; Manguntara, La (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Good online news writing for new students focuses on providing material about procedures, formats, techniques, how to choose the title and how to write a good article for journalism by applying the 5W+1H theory (Where, When, Why, Who, What and How). The main topic of discussion is the introduction and consolidation of material related to writing online news with appropriate grammar/sentence patterns. The format for writing good news is then followed by techniques for writing good news by paying attention to several aspects based on existing theories. Next is how to make a good news headline as well as a guide to several examples of making good news in the news. Consolidation of the material as well as evaluation of participants' writing results is the final activity of this service.